Adaptation and sustainability of water management for rice agriculture in temperate regions: The Italian case‐study. (30th July 2019) - Zampieri, Matteo; Ceglar, Andrej; Manfron, Giacinto; Toreti, Andrea; Duveiller, Gregory; Romani, Marco; Rocca, Cesare; Scoccimarro, Enrico; Podrascanin, Zorita; Djurdjevic, Vladimir
Abstract: We review, analyse, and discuss the recent evolution and the future sustainability of rice paddy fields in Italy—the largest European producer—using outcomes from available literature and new analysis of agricultural statistics from local authorities, land‐use and surface temperature data from remote sensing, hydrological and climate data from observations, and numerical models. We show that Italy can be considered a good representative for rice cultivation in temperate regions that are not freshwater‐limited. However, this situation is changing. We report strong evidence linking the largest European reduction of seasonal surface water that have gradually occurred since 2000 over the rice cultivation area of Northern Italy, to the change in paddy management from traditional continuous flooding to a less greenhouse‐gases‐emitting practice, that is, dry‐seeding with postponed flooding. This change was accompanied by several improvements in agro‐practices and crop varieties. Concurrently, regional climate rapidly shifted towards sunnier weather conditions that partly contributed to higher rice yields and stability, decoupling yields from inter‐annual climate variability, but also reducing water availability. In Northern Italy, a complete shift of rice cultivation towards dry‐seeding is not compatible with seasonal water availability, and a number of drawbacks, with respect to the traditional wet seeding, are also identified from literature review. Therefore, in the context of near‐term climate change, sustainable rice cultivation in the middle latitudes seems achievable (without limiting production and/or increasing volatility) by balancing traditional and dry‐seeding.